New fairy armadillo records from the late Miocene (Chasicoan Stage/Age) of central Argentina - Barasoain, Daniel (2019)
Fairy armadillos or “pichiciegos” (Cingulata, Chlamyphoridae) are represented by two monospecific extant genera, Chlamyphorus truncatus Harlan, 1825, and Calyptophractus retusus Burmeister, 1863. These taxa are among the most rare and elusive mammals. Molecular analyzes suggest their presence since the Early Miocene. Recently, it was described the first fossil record of this lineage, MMH-CH-87-7-100, a new genus and species coming from Late Miocene deposits of Arroyo Chasicó Formation (= Cerro Azul Formation; Chasicoan Stage/Age), at Arroyo Chasicó, Province of Buenos Aires. Its inclusion on a phylogenetic analysis reflected the monophyletic status of the Chlamyphorinae and its relation as sister group of both extant species. We report here new specimens recovered from other sites of central Argentina. In both cases, bearing levels also correspond to the Late Miocene (Chasicoan Stage/Age). GHUNLPam3190 is a fragment of rump plate coming from Cerro Azul Formation, at Cerro La Bota site, Province of La Pampa. Four specimens come from Loma de Las Tapias Formation, at Loma de Las Tapias site, Province of San Juan: INGEO-PV-022, a fragment of rump plate with most part of the pelvis fused; PVSJ 156a, a fragment of dorsal carapace with several articulated osteoderms; and INGEO-PV-001 and PVSJ157a, several isolated mobile and fixed osteoderms. These specimens show clear affinities with that of Arroyo Chasicó and possibly belong to closely related taxa. In addition, all available fossil materials show clear morphological differences compared to extant representatives (e.g., carapace structure, ornamentation of the osteoderms, rump plate morphology), suggesting a higher fairy armadillos diversity during Late Miocene.